Determinação voltamétrica de analitos de interesse farmacêutico utilizando um eletrodo de diamante dopado com boro - Sartori, Elen Julciléia Romão (2009)
The development of electroanalytical procedures for acetylsalicylic acid (ASA), propranolol (PROP), atenolol and sildenafil (Viagra®) in pharmaceutical formulations using a boron doped diamond (BDD) electrode, square wave and differential pulse voltammetric techniques are described. ASA was directly determined in a 0.01 mol L-1 H2SO4 solution without the need of a previous alkaline hydrolysis step with the BDD electrode and square wave voltammetry (SWV). The analytical curve was linear in the ASA concentration range 2.5 × 10-6 to 1.0 × 10-4 mol L-1 with a detection limit of 2.0 × 10-6 mol L-1. Then, the analytical determination of PROP was carried out in a 0.1 mol L-1 H2SO4 solution using a cathodically pre-treated BDD electrode employing SWV. The analytical curve was linear in the PROP concentration range 2.0 × 10-7 to 9.0 × 10-6 mol L-1 with a detection limit of 1.8 × 10-7 mol L-1. The determination of atenolol was accomplished in 0.5 mol L-1 NaNO3 (pHcond 1.1 adjusted with concentrated HNO3) on a cathodically pre-treated BDD electrode employing SWV. The analytical curve was linear in the atenolol concentration range from 2.0 × 10-6 to 4.1 × 10-5 mol L-1 with a detection limit of 9.3 × 10-7 mol L-1. Finally, a procedure for the determination of sildenafil in 0.1 mol L-1 H2SO4 on a cathodically pre-treated BDD electrode employing differential pulse voltammetry was developed. The analytical curve was linear in the sildenafil concentration range 7.3 × 10-7 to 7.3 × 10-6 mol L-1 with a detection limit of 4.8 × 10-7 mol L-1.